Equating Two Health-related Quality of Life Instruments Applied to Cancer Survivors Who Underwent Palliative Care - Bongsam Choi; Heesu Kim; Sunhwi Bang; Byunggwan Kim; Jaekwang Shim (Korean Research Society of Physical Therapy, 2023)
Background: Equating is a statistical procedure used to create a common measurement scale across two instruments. Item-level information should be taken into consideration so that scores can communicate interchangeably across the instruments. Objects: To investigate a common measurement scale across two health-related quality of life questionnaires (HRQOL) applied to various cancer survivors who underwent palliative care in healthcare institutions. Methods: A total of 139 cancer survivors who underwent palliative care were recruited from two rehabilitation hospitals and an oriental medicine hospital. Participants consisted of various cancer survivors who presented to the sites for palliative care. They were asked to fill out Korean versions of the World Health Organization Quality of Life (WHOQOL-BREF) and EuroQOL-5 dimension (EQ-5D) questionnaires following the palliative care. For the item level comparison, the Rasch rating scale model was used to investigate how participants regarded individual test items of two instruments in relation to item difficulty calibrations. Results: All items except the three items fit the Rasch model. One item (anxiety/depression) of the EQ-5D and two items (dependence on medical aids and negative feelings) of the WHOQOL- BREF are misfit. The WHOQOL-BREF targets the survivors well, while the EQ-5D is able to target the survivors with lower HRQOL levels with some ceiling effects. By inspecting the item difficulty calibrations of the two instruments, five items of the WHOQOL-BREF are selected as common items in relation to the EQ-5D. These five items are considered compatible with each other. Differential item functioning (DIF) analysis reveals that the healthcare item of the WHOQOL-BREF vs the self-care item of the EQ-5D exhibits significant DIF. Conclusion: Findings suggest that one paired item should be taken into consideration when equating the WHOQOL-BREF and the EQ-5D applied to cancer survivors who underwent palliative care.